2015
DOI: 10.1016/s2215-0366(14)00071-6
|View full text |Cite
|
Sign up to set email alerts
|

Punishment and psychopathy: a case-control functional MRI investigation of reinforcement learning in violent antisocial personality disordered men

Abstract: SummaryBackground Men with antisocial personality disorder show lifelong abnormalities in adaptive decision making guided by the weighing up of reward and punishment information. Among men with antisocial personality disorder, modifi cation of the behaviour of those with additional diagnoses of psychopathy seems particularly resistant to punishment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
73
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(79 citation statements)
references
References 38 publications
6
73
0
Order By: Relevance
“…Importantly, the decreased activity in the dACC was associated with interpersonal-affective dimensions of psychopathy (97). However, Gregory et al (62) found more divergent neural activity in ASPD and psychopathy in a reversal learning setting. The researchers found that psychopathic individuals responded to punishment with increased activation of the posterior cingulate cortex and insula, whereas ASPD subjects showed decreased activity in these areas (62).…”
Section: Functional Mri Findings In Aspdmentioning
confidence: 93%
See 1 more Smart Citation
“…Importantly, the decreased activity in the dACC was associated with interpersonal-affective dimensions of psychopathy (97). However, Gregory et al (62) found more divergent neural activity in ASPD and psychopathy in a reversal learning setting. The researchers found that psychopathic individuals responded to punishment with increased activation of the posterior cingulate cortex and insula, whereas ASPD subjects showed decreased activity in these areas (62).…”
Section: Functional Mri Findings In Aspdmentioning
confidence: 93%
“…However, Gregory et al (62) found more divergent neural activity in ASPD and psychopathy in a reversal learning setting. The researchers found that psychopathic individuals responded to punishment with increased activation of the posterior cingulate cortex and insula, whereas ASPD subjects showed decreased activity in these areas (62). Further evidence for divergent neural correlates was provided by Murray, Shaw, Forbes, and Hyde (96) who showed that antisocial behavior, but not CU traits, was associated with decreased activity in the ventral striatum and dorsolateral prefrontal cortex during reward anticipation.…”
Section: Functional Mri Findings In Aspdmentioning
confidence: 96%
“…Most notably, the amygdala, the ventromedial (VMPF) and orbitofrontal cortex (OFC) (Blair, 2008), and the extended neural circuitry that is related to the broader paralimbic area of the brain (Kiehl, 2006) are among these regions. Functional MRI research also found, for example, reduced activity in the anterior cingulate cortex, the anterior insula and ventral striatum in offenders with comorbid ASPD and psychopathy relative to those with only ASPD (Gregory et al, 2015;Hosking et al, 2017). The correlation of psychopathic traits with dysregulation of attentional processes is another prominent example of cognitive deficiencies believed to differentiate this group from other antisocial populations.…”
Section: The Biocognitive Approach To Classification Of Antisocial Bementioning
confidence: 96%
“…Punishment sensitivity plays an important role in normal learning, decision making as well as emotion (Corr, 2004). Differences in sensitivity to punishment have been implicated in the aetiology or maintenance of a range of psychopathologies including conduct disorder (Briggs-Gowan et al, 2014;Dadds & Salmon, 2003), drug and behavioural addictions (Vanderschuren, Minnaard, Smeets, & Lesscher, 2017), eating disorders (Monteleone et al, 2018), psychopathy (Blair, Morton, Leonard, & Blair, 2006;Gregory et al, 2015), and depression (Elliott et al, 1996;Eshel & Roiser, 2010). Moreover, punishment sensitivity is an increasingly popular measure of the motivation to engage in drug-seeking and drug-taking (Augier et al, 2018;Deroche-Gamonet, Belin, & Piazza, 2004;Kasanetz et al, 2012;Marchant et al, 2018;Pascoli, Terrier, Hiver, & Luscher, 2015;Vanderschuren & Everitt, 2004;Vanderschuren et al, 2017).…”
mentioning
confidence: 99%